1 W.W. Hening, Laws of Va. from First Sess. of Legis. in 1619, Act LVI at 174-5 (1823) - (:unkn) unknown (My University, 1631)
Required an annual muster of the men, women, and children of the plantations by the plantation commanders. Information collected: age, country and towns of birth, the ship they travelled upon. Also "of armes and munition, corne, cattle, hoggs, goates, barques, boates, gardens, and orchards."
Keywords: REGISTRATION